(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article talks about teaching the culture of human relations to the next generation by forming the manners and skills of communicative communication in students from the primary grade, and special attention is paid to the moral qualities characteristic of national values. Communication is an important form of interaction that shows the inner and outer world of a person . Through communication, a person communicatively expresses his views, imagination and feelings about the external world, the social, economic, and spiritual life of society . With the emergence of human society, the culture of communication between people was felt as one of the necessary needs. The mutual communication of members of the society is the basis for all-round development of this society.